Application of WeChat platform combined with problem-based learning teaching method in standardization training for proctology specialist (微信平台联合PBL教学法在肛肠学科规范化培训教学中的应用) - LAI Lixia (来丽霞); YU Qiang (郁强); MA Huangfu (马凰富); LI Jianan (李佳楠); SONG Xinbo (宋新波); WANG Yanmei (王晏美); FAN Xueshun (范学顺); WANG Yanzhi (王艳芝) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the effect of WeChat platform combined with problem-based learning (PBL) teaching method in standardization training for proctology specialist. Methods Totally 60 medical specialists who required standardization training were randomly divided into two groups, with 30 cases in each group. The observation group adopted wechat platform combined with PBL teaching method, while the control group adopted traditional teaching method. After teaching, the written test, operation skill and clinical competency were evaluated comprehensively. Results Scores of written test and operation skill in the observation group were higher than those in the control group (P＜0. 05). All indicators of clinical competence including reasoning ability, information processing capability, interpersonal communication skills and overall coordination ability in the observation group were higher than those in the control group (P＜0. 05). Conclusion WeChat platform combined with PBL teaching method in the standardization training can significantly improve the theoretical knowledge mastery and practical operation skills of specialists. The combined teaching method contributes to the establishment of standardized thinking mode in clinical diagnosis and treatment. (目的 探讨微信平台联合以问题为基础的学习(PBL)教学法在肛肠学科规范化培训教学中的应用效果。方法 将60例规范化培训学员随机分为观察组和对照组, 各30例。对照组采用传统教学法, 观察组采用微信平台联合PBL教学法。比较2组培训考核成绩以及临床胜任力。结果 观察组笔试和技能操作成绩均得分均高于对照组, 差异有统计学意义(P＜0. 05)。观察组临床推理能力、信息处理能力、人际交流能力、整体协同能力得分均高于对照组, 差异有统计学意义(P＜0. 05)。结论 微信平台联合PBL教学法在肛肠学科住院医师规范化培训中应用效果显著, 有助于提高规范化培训医生的理论知识掌握能力和实践操作技术水平, 帮助建立规范的临床诊疗思维模式。)